THE EFFECT OF SERVICE QUALITY AND PRICE AND FACILITIES ON PATIENT SATISFACTION IN HOSPITAL HARAPAN PEMATANGSIANTAR - Panjaitan, Hadi; Dangel, Jonathan; Saragih, Jopinus; Mayanta Tarigar, Hendri; K Tarigan, Adrian (International Conference on Health Science, Green Economics, Educational Review and Technology, 2021)
The research design used in writing this thesis is library research. The population of this study were all patients at Harapan Pematangsiantar Hospital. The sample of this study were outpatients at Harapan Pematangsiantar Hospital. The data collection technique in this study was the documentation method, namely data collection by recording data related to the problem to be studied by searching data in the form of books, electronic media, and so on. The data analysis used by the author is qualitative. Respondents with male and female gender were 5 people (50.0) and respondents with ages 35-39 years were 4 people (40.0). While the majority of private employees work as many as 8 people (80.0). While the length of stay for less than three days there were 6 people (60.0). So it can be concluded that inpatients at Harapan Pematangsiantar Hospital in this study the number of males is balanced with females, more are aged 3-39 years, work as private employees and length of stay is less than three days. In this study the authors asked 10 inpatients directly for their responses regarding the quality of inpatient service at Harapan Pematangsiantar Hospital which was very good according to their responses on the questionnaire sheet provided by the author. Respondents' responses as inpatients regarding the price of treatment at the Harapan Hospital were quite satisfactory because they were in accordance with the services provided. Respondents' responses as inpatients regarding satisfaction in the facilities provided by Harapan Hospital were quite satisfactory for patients because they were provided properly for the comfort of the patients.